Establishment and characterisation of CRTC1 knockout in rodent hippocampal neurons - Koh, Tyler Bo Kai (2017)
CRTC1 is a transcriptional modulator that is crucial for learning and memory. At present, a conditional knockout mouse has never been studied either in neuronal cultures or live animals. In this report, we propose the use of a single lentiviral vector to deliver Cas9 and guide RNAs (gRNAs) into neurons to knockout the expression of CRTC1 in hippocampal neurons in vitro and in vivo. Our lentiviral vectors efficiently knockouts CRTC1 expression in primary hippocampal cultures while results are pending for in vivo microinjections of the virus. A preliminary study on the effects of neurons lacking CRTC1 expression indicate an increase in spine area and length while the distribution and density of spines remain unaltered.